2013
DOI: 10.1080/10345329.2013.12035992
|View full text |Cite
|
Sign up to set email alerts
|

An Overview of Current Initiatives to Improve Child Witness Interviews about Sexual Abuse

Abstract: This comment provides an overview of the main barriers to eliciting quality evidence from child witnesses in sexual abuse cases and recent attempts within several Australian jurisdictions to overcome these barriers. The comment takes a constructive approach. Recommendations relate to five themes: adoption of a narrative framework, quality of training, interviewer workplace climate, prosecutor feedback, and ongoing case tracking and evaluation. While the focus is on child witnesses, the recommendations also app… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 28 publications
0
18
0
Order By: Relevance
“…Ground rule efficacy has typically been evaluated by examining children's brief (one or two word) responses to incomprehensible, complicated, or misleading questions (see, for example, Endres, Poggenpohl, & Erben, ; Nesbitt & Markham, ; Peterson & Grant, ; Saywitz, Snyder, & Nathanson, ). In forensic situations, however, investigative interviewers are specifically trained to avoid such prompts and are instead taught to emphasize non‐misleading open questions (such as “Tell me more about that part.” and “What happened next?”) which elicit lengthier, narrative responses (Lamb et al, ; Powell, ). Minimal research has investigated whether ground rules still provide benefits over the duration of a narrative interview.…”
Section: Introductionmentioning
confidence: 99%
“…Ground rule efficacy has typically been evaluated by examining children's brief (one or two word) responses to incomprehensible, complicated, or misleading questions (see, for example, Endres, Poggenpohl, & Erben, ; Nesbitt & Markham, ; Peterson & Grant, ; Saywitz, Snyder, & Nathanson, ). In forensic situations, however, investigative interviewers are specifically trained to avoid such prompts and are instead taught to emphasize non‐misleading open questions (such as “Tell me more about that part.” and “What happened next?”) which elicit lengthier, narrative responses (Lamb et al, ; Powell, ). Minimal research has investigated whether ground rules still provide benefits over the duration of a narrative interview.…”
Section: Introductionmentioning
confidence: 99%
“…The objective of this research was to advance knowledge about potential modalities of delivery for effective refresher training that could be offered in the context of child investigative interviewing. As we know, interviewing children is a difficult task, and best practices tend to diminish over time after conclusion of training (Ford et al, 2018;Lamb, 2016;Powell, 2013). It is therefore important to better understand the effect of various post-training refreshers on inter ie ers abilities to follow a protocol and ask effective questions.…”
Section: Discussionmentioning
confidence: 99%
“…Investigative interviewing is a complex skill that necessitates specialized training (Powell, 2013;Powell, Wright, et al, 2010). Experts have identified that the training delivered to child forensic interviewers appears to improve knowledge about good interviewing practices but transfer to on-the-job skills is incomplete or fades over time (Lamb, 2016;Powell, 2013;cf Lindholm et al, 2016). Questions about transfer of training are age-old in the field of organizational psychology (see Bell et al, 2017 for a review), but are comparatively emerging in the literature on training investigative interviewers.…”
Section: In Er Ie Er Po -Training Performancementioning
confidence: 99%
“…In particular, the reduction of leading yes-no questions was especially encouraging. Spaced learning conditions and immediate feedback, typical of online training programs, are superior to blocked learning and delayed feedback (Powell, 2008(Powell, , 2013. Avenues for further research in this area include the development and testing of an online module for teachers concerning effective questioning.…”
Section: Implications and Conclusionmentioning
confidence: 96%